The early modern Medea Medea in English literature, 1558 - 1688 - Heavey, Katherine 1982-2022 (Early modern literature in history, 2014)
"The classical witch and infanticide Medea was a figure of potent interest to early modern English authors, and she was adapted or alluded to by a wealth of major and lesser-known writers in the period, including Shakespeare, Jonson, Spenser, James Shirley, and Robert Greene. Medea's story was a significant one for early modern translators, but the bloody revenge she takes on her faithless husband Jason also fascinated authors of tragedy, political writing, and even comedy. This is the first book-length study of early modern English approaches to Medea, in the period 1558-1688. Encompassing poetry, prose and drama, and translation, tragedy, comedy and political writing, this book explores how early modern authors were at once fascinated and repelled by Medea's terrible power, and how they sought to represent but also negotiate her ruthless cruelty, to caution and entertain their readers and audiences"..